Hubungan antara Konformitas dengan Perilaku Agresif Siswa yang Bermain Game Online - Andrian, Deny; Setiawan, Agus; Lestari, Farikha Wahyu (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2025)
The phenomenon of game online in students often causes emotional instability and tends to conform with other students and even peers so that it can cause aggressive behavior, both verbally and physically. This study aims to determine the relationship between conformity and aggressive behavior in students who play online games at SMA N 1 Banjarharjo. The method used in this study is quantitative by involving 55 grade XI students who play online games at SMA N 1 Banjarharjo which were obtained using purposive sampling techniques. The research data were tested using Product Moment correlation data analysis. Based on the results of data analysis, it was found that there was a relationship between conformity and aggressive behavior in students who play online games at SMA N 1 Banjarharjo with a sig. value of 0.006 <0.05 and the calculated r value> r table is 0.368> 0.266 which means there is a positive and significant relationship between conformity and aggressive behavior of students who play online games at SMA N 1 Banjarharjo.